Image and presence : a Christological reflection on iconoclasm and iconophilia - Carnes, Natalie (Encountering traditions., 2018)
Images increasingly saturate our world, making present to us what is distant or obscure. Yet the power of images also arises from what they do not make present - from a type of absence they do not dispel. Joining a growing multidisciplinary conversation that rejects an understanding of images as lifeless objects, this book offers a theological meditation on the ways images convey presence into our world. Just as Christ negates himself in order to manifest the invisible God, images, Natalie Carnes contends, negate themselves to give more than they literally or materially are. Her Christological reflections bring iconoclasm and iconophilia into productive relation, suggesting that they need not oppose one another.0Investigating such images as the biblical golden calf and paintings of the Virgin Mary, Carnes explores how to distinguish between iconoclasms that maintain fidelity to their theological intentions and those that lead to visual temptation. Offering ecumenical reflections on issues that have long divided Protestant, Catholic, and Orthodox traditions, 'Image and Presence' provokes a fundamental reconsideration of images and of the global image crises of our time.